Strategi Dakwah Pada Masyarakat Multikultural Di Desa Singgahan Kabupaten Ponorogo - Tsalits Maratun Nafiah (IAIN Padangsidimpuan, 2021)
The dynamics of the development of society is now more advanced. Indonesia as a multicultural country is rich in diversity ranging from religion, ethnicity, language, and socio-culture. In a multicultural society, of course, da'wah is faced with various challenges and complex problems. Moreover, Indonesia is currently facing a very worrying situation, namely the Covid-19 pandemic. So in achieving the mission, namely the delivery of da'wah messages, he needs a strategy in preaching. The purpose of this study was to determine the da'wah strategy used for multicultural communities during the COVID-19 pandemic in Singgahan Village. This study uses a qualitative descriptive research approach. The results showed that there were two da'wah strategies carried out, namely the first by conventional or face-to-face da'wah. This method is carried out with the aim of proselytizing the elderly while still complying with health protocols and limiting the number of worshipers. The second strategy is done online through social media. This strategy is applied to teenagers and people who are technology literate and understand social media. It is hoped that this strategy will be able to minimize the spread of Covid-19.Keywords: Da'wah, Multicultural Society, Covid-19 Pandemic